Performance of a lateral pelvic cluster technical system in evaluating running kinematics. Issue 9 (14th June 2016) - Liew, Bernard X.W.; Morris, Susan; Robinson, Mark A.; Netto, Kevin
Abstract: Valid measurement of pelvic and hip angles during posterior load carriage gait task requires placement of pelvic markers which will not be occluded or physically displaced by the load. One solution is the use of pure lateral pelvic clusters to track the pelvis segment. However, the validity of this method has not been compared against pelvic marker systems recommended by the International Society of Biomechanics (ISB) during high impact tasks, such as running. The purpose of this study was to validate the lateral tracking pelvic clusters against the ISB pelvis during running. Six participants performed overground running at a self-selected running speed with shoes. Three dimensional motion capture and synchronised in-ground force plates were used to determine lower limb joint angles and gait events respectively. Two biomechanical models were used to derive pelvic segment and hip joint angles. The ISB pelvis used the anterior and posterior iliac spines as anatomical and tracking markers, whilst the other model used lateral pelvic clusters as tracking markers. The between participant averaged coefficient of multiple correlation suggested good to excellent agreement between the angle waveforms generated from the two marker protocols. In addition, both marker protocols had similar sensitivity in detecting three dimensional pelvic and hip joint angles during the stance phase. This study suggests that in the event posterior load carriage is involved in running gait, pelvic and hip kinematics can be measured by the use of lateral pelvic clusters.